Intergenerational Mobility in American History: Accounting for Race and Measurement Error - Ward, Zachary (American Economic Review, 2023)
A large body of evidence finds that relative mobility in the US has declined over the past 150 years. However, long-run mobility estimates are usually based on White samples and therefore do not account for the limited opportunities available for nonwhite families. Moreover, historical data measure the father’s status with error, which biases estimates toward greater mobility. Using linked census data from 1850 to 1940, I show that accounting for race and measurement error can double estimates of intergenerational persistence. Updated estimates imply that there is greater equality of opportunity today than in the past, mostly because opportunity was never that equal. (JEL J15, J62, N31, N32)